EFEKTIVITAS APLIKASI PENDAFTARAN PESERTA DIDIK BARU SECARA ONLINE OLEH BALAI PENJAMINAN MUTU PENDIDIKAN PROVINSI SUMATERA UTARA (TEORI AIETA : AWARENESS, INTEREST, EVALUATION, TRIAL, DAN ADOPTION) - Aisyah, Siti; Azmi, Raisa (Politeknik Bisnis Indonesia, 2024)
This research focuses on the effectiveness of the online new learner registration application developed by the Education Quality Assurance Center of North Sumatra Province. The AIETA theory (Awareness, Interest, Evaluation, Trial, Adoption) is used to understand the process of application acceptance by the community. In this study, AIETA theory is used to understand the stages of application acceptance by the community. These stages include Awareness of the app, Interest in using the app, Evaluation of the app, Trial of the app, and Adoption of the app. Thus, this study shows that the online new learner enrollment application has the potential to increase the effectiveness of new learner enrollment, but some problems need to be fixed. Thus, this application can be one of the effective solutions in improving the effectiveness of new student admissions in North Sumatra Province. The results of the interview show that the community has been able to adjust to the online new student registration system, and this system makes it easier for parents of students to register their children as prospective new students, makes it easier to find information about the school's profile and excellence and the admission of new students will be more practical, effective and efficient.